SstI Polymorphism of the Apolipoprotein CIII Gene in Iranian Hyperlipidemic Patients: A Study in Semnan Province - Bandegi, Ahmad Reza (Mashhad University of Medical Sciences, 2011)
OBJECTIVE(S): The Sst-I polymorphic site on the 3' untranslated region of the apo CIII gene, has been previously reported to be associated with hypertriglyceridemia. The aim of the present study was to explore the association between Sst-I polymorphism with plasma lipid and lipoprotein levels in hyperlipidemic (HLP) patients from Semnan province, Iran. MATERIALS AND METHODS: Genomic DNA was prepared from 76 patients with HLP and 75 matched healthy subjects. DNA samples were amplified by polymerase chain reaction. The samples were analyzed by restriction fragment length polymorphism (RFLP) method using SstI enzyme. RESULTS: The genotype and allelic frequencies for this polymorphism were significantly different between HLP and normolipidemic groups (P< 0.002). Plasma triglyceride (TG) level was higher in both groups, in S2S2 genotype was more than in the S1S1and S1S2 genotypes, however, there was no significant difference in comparison with the control group. Subjects with S1S2 + S2S2 genotypes in compare to S1S1 genotype had odd ratio of 2.8 (95% CI: 1.41-5.56, P< 0.003) for developing hypertriglyceridemia. CONCLUSION: The results showed that the presence of rare S2 allele was associated with change in TG level in the selected population.